2017
DOI: 10.1371/journal.pone.0176170
|View full text |Cite
|
Sign up to set email alerts
|

45S rDNA external transcribed spacer organization reveals new phylogenetic relationships in Avena genus

Abstract: The genus Avena comprises four distinct genomes organized in diploid (AA or CC), tetraploid (AABB or AACC) and hexaploid species (AACCDD), constituting an interesting model for phylogenetic analysis. The aim of this work was to characterize 45S rDNA intergenic spacer (IGS) variability in distinct species representative of Avena genome diversity–A. strigosa (AA), A. ventricosa (CvCv), A. eriantha (CpCp), A. barbata (AABB), A. murphyi (AACC), A. sativa (AACCDD) and A. sterilis (AACCDD) through the assessment of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 51 publications
(70 reference statements)
0
11
0
Order By: Relevance
“…First, based on the asymmetrical karyotype with a preponderance of heterobrachial chromosomes species, Rajhathy 51 proposed that A. ventricosa was the C genome donor towards hexaploid oat. Recent studies also provided support for A. ventricosa being the ancestral Avena genome based on 45 S rDNA external transcribed spacer organization variability 52 and based on ITS1-5.8 SITS2 sequence variability 53 . Second, A. canariensis was the only diploid oat species with denticulate lemma tips, which is a morphological feature in common with hexaploid oat 54 .…”
Section: Discussionmentioning
confidence: 95%
“…First, based on the asymmetrical karyotype with a preponderance of heterobrachial chromosomes species, Rajhathy 51 proposed that A. ventricosa was the C genome donor towards hexaploid oat. Recent studies also provided support for A. ventricosa being the ancestral Avena genome based on 45 S rDNA external transcribed spacer organization variability 52 and based on ITS1-5.8 SITS2 sequence variability 53 . Second, A. canariensis was the only diploid oat species with denticulate lemma tips, which is a morphological feature in common with hexaploid oat 54 .…”
Section: Discussionmentioning
confidence: 95%
“…Kellogg and Bennetzen (2004) put forward that this variation was the outcome of a set of highly active processes, including gene duplication and deletion, chromosomal duplication followed by gene loss, amplification of retrotransposons separating genes, and genome rearrangement; the latter process often follows hybridization or polyploidy. Rodrigues et al (2017) suggested that the loss of the C genome sequence might be correlated with differences in the parental genome size in polyploid species of Avena. Indeed, the C genome is larger than the A genome (Bennett and Leitch 2012).…”
Section: Genetic Relationships Of Species Of Avena and The Hexaploid mentioning
confidence: 99%
“…Despite widespread occurrence and economic value of most cereals from the Aveneae / Poeae tribe, their genomes still remain insufficiently studied [14, 15]. Due to the agricultural significance, oat species have become the subject of complex investigation, and extensive molecular studies have largely clarified diversity and evolution of the genus Avena [1620]. Phylogenetic studies in recent decades, mostly based on analyses of different DNA sequences from both plastid regions and nuclear ribosomal regions, have helped to clarify the evolutionary relationships within the Aveneae / Poeae complex [4, 5, 15, 2123].…”
Section: Introductionmentioning
confidence: 99%